The New Relationship between the United Kingdom and the European Union
IX, 466 p. 1 illus.
Keywords: Brexit has reshuffled the cards of the relationship between the United Kingdom and the European Union. It is a one in a lifetime event, which ended nearly 50 years of EU Membership. EU law as such no longer applies in the United Kingdom and British citizens and companies no longer benefit from its advantages. Part of the previous regime has however been maintained (at times with amendments) through the series of treaties negotiated between the UK and the EU in 2019 and 2020, in particular the Trade and Cooperation Agreement of 2020, to which the 2023 Windsor Agreement can be added. The end result is a legal regime which is perhaps even more complex than EU law itself. This book aims to provide the reader with a clarification of this legal regime as well as provide context to it and suggestions to improve it. All key topics are covered, such as citizens of the EU in the UK and British citizens in the EU, trade in goods and in services, criminal justice, public procurement, Northern Ireland, the UK overseas territories, the dispute settlement, security and defence, international trade agreements of the UK post-Brexit, environmental protection, European civil justice, financial services, education and research, and the European offices of the UK local authorities and devolved administrations after Brexit. All the chapters follow, wherever possible, the same triadic structure. The first part looks at the regime prior to Brexit; the second part analyses the current regime; and the third part discusses ongoing and predictable trends. The concluding chapter attempts to identify some themes likely to impact on the forthcoming preparation of the 2026 review.